2023
DOI: 10.3390/cancers15174281
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery in Non-Small Cell Lung Cancer: Where Do We Stand?

Lawek Berzenji,
Wen Wen,
Stijn Verleden
et al.

Abstract: In the last two decades, robotic-assisted thoracoscopic surgery (RATS) has gained popularity as a minimally invasive surgical (MIS) alternative to multi- and uniportal video-assisted thoracoscopic surgery (VATS). With this approach, the surgeon obviates the known drawbacks of conventional MIS, such as the reduced in-depth perception, hand-eye coordination, and freedom of motion of the instruments. Previous studies have shown that a robotic approach for operable lung cancer has treatment outcomes comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 95 publications
0
0
0
Order By: Relevance
“…The original intention of robot-assisted surgery was to perform remote surgery on soldiers on the battlefield ( 10 ). Due to the high speed, high reliability, and low latency advantages of 5G networks, the clinical application of robotic surgery has accelerated significantly ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The original intention of robot-assisted surgery was to perform remote surgery on soldiers on the battlefield ( 10 ). Due to the high speed, high reliability, and low latency advantages of 5G networks, the clinical application of robotic surgery has accelerated significantly ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive approaches, such as video-assisted thoracoscopic surgery (VATS) and robot-assisted thoracoscopic surgery (RATS), have become standard therapies for early-stage lung cancer [ 1 ]. Pulmonary lobectomy and segmentectomy are the two main types of anatomical resections for lung cancer, and segmentectomy has recently been demonstrated to be a valuable alternative to lobectomy [ 2 ]. Anatomical segmentectomy is a more challenging procedure than lobectomy, since the anatomy of pulmonary segments is complex.…”
Section: Introductionmentioning
confidence: 99%
“…The JCOG0802/WJOG4607L Japanese large-scale randomized trial and the CALGB/Alliance 140503 trial conducted in the United States have shown the potential of sublobar resections for the curative treatment of early-stage non-small cell lung cancer [ 9 , 10 ]. Multiportal VATS, RATS, and uniportal VATS have become more common surgical techniques [ 1 , 2 ], where 3D CT images have been frequently used as surgical guidance for a minimally invasive resection of untouchable and invisible small tumors. Furthermore, various kinds of software have been developed worldwide and marketed mainly for preoperative and intraoperative simulations to reconstruct 3D CT images [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%